Efficiency of coconut husk as agricultural adsorbent in removal of chromium and nickel ions from aqueous solution - S. F. M., Hanafiah; N. F. M., Salleh; N. A., Ghafar; N. M., Shukri; N. H. N., Kamarudin; M., Hapani; Rohayu, Jusoh (IOP Publishing Ltd., 2020)
Coconut husk is categorized as the agriculture waste product that can act as biosorbent material. In this study, coconut husk was used as an adsorbent to investigate the ability of this agricultural by-product to adsorb nickel and chromium. In this experiment, nickel and chromium ion were adsorbed in batch adsorption experiment using different parameters; effect of contact time (30, 60, 90, 120, 150) minutes, pH (3, 5, 7, 9,11), adsorbent dosage (1.0, 1.5, 2.0, 2.5, 3.0) g. An optimum level of adsorption for chromium by using raw coconut husk occurred at 90 minutes of contact time, pH 3, and dosage of adsorbent of 1.5g. Meanwhile, optimum adsorption of nickel occurred at contact time of 90 minutes, with pH 5, adsorbent dosage of 1.5g. Statistical analysis showed that there was a significant mean difference between percent removal of chromium (Cr) and nickel (Ni). There was a significant mean difference between dosage and percent removal of chromium ions. In conclusion, both raw and acid-treated coconut husk can adsorb nickel and chromium ions from aqueous solutions.